Malays, China and Indian Ethnicities: A Case Study of Art and Ethnography Content Analysis and Multiculturalism on Upin-Ipin Animation - Wenny Maya Arlena; Ni Gusti Ayu Ketut Kurniasari (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2013)
This study aims to describe the ethnic group or tribe is a group of people whose members identify themselves with one another, usually based on lineage are considered the same as culture, language, religion traits, behaviors, or biological. Ethnicity is a fundamental factor in human life, interactions and intrinsic property of a group. The method of research used content analysis approaches and ethnographic art. The results showed determination by mixing or races as “Peranakan”: for a mixture of Malay race with China, people who are determined according to their religion, for Malays in Malaysia it meant that the Muslim bumiputera, “the Mestis” for Hispanic mix by bumiputera. Upin Ipin-released on September 14, 2010 in Malaysia and produced by Les’ Copaque. The results of this study show Upin-Ipin filled with simplicity in bringing Islamic values, education, manners, and respect among fellow was meant for all people of good Malaysian nation or religion. Good relations between different cultures (Malay, Chinese, Indian) were described in this animated film. Upin-Ipin animated movie brings the perfect image and message, ie, with different cultures can create a good relationship with the harmony of differences in unity and simplicity.